Development and validation of a headspace gas chromatographic method for determination of residual solvents in Bosentan monohydrate - Sivasaikiran B.; Nayudamma Chowdary Y.; Sreelakshmi V.; Shrivastava S.K.; Pugazhendhy S. (My University, 2025)
A simple and sensitive method for the simultaneous determination of methanol, ethanol, acetone, acetonitrile and toluene in Bosentan monohydrate by headspace techniques with FID detection is described. Bosentan monohydrate is a dual endothelin receptor antagonist used in the treatment of pulmonary artery hypertension (PAH). In order to increase productivity of drug analysis in the pharmaceutical industry, an efficient and sensitive HSGC method was successfully developed and validated for the determination of 44 classes 2 and 3 above mentioned solvents of International Conference of Harmonization (ICH) guideline Q3C, as residual solvents in drug substance. Based on Good manufacturing practices, measuring residual solvents is mandatory for the release testing of all active pharmaceutical ingredients. The method was validated for repeatability, linearity, limit of detection, limit of quantification and recovery according to the International Conference on Harmonization guidelines. The method validation results indicate that the method is accurate, precise, linear and sensitive for solvents assessed. Excellent results were obtained, within the globally accepted validation reference values, particularly taking into account the low concentration levels investigated.